Retrospective analysis of the utilisation of DNA analyses in the identification of human remains at Salt River Mortuary (Cape Town, South Africa) - Kambowo, Sophy Celine (Department of Pathology, 2025)
Post-mortem human identification is crucial for medico-legal investigations and for social justice. Unfortunately, many people remain unidentified, particularly in developing countries. The use of forensic DNA profiling is a reliable method for human identification and was legislated in South Africa in January 2015. However, the use and success of DNA as an identification tool at Salt River Mortuary (SRM) in South Africa are unknown. Medico-legal case files were reviewed from all 3696 cases admitted in 2015, to evaluate the use of DNA in identifying human remains at SRM immediately after the implementation of the ‘DNA Act'. While 213 (5.76 %) cases were admitted in 2015 without an alleged identity, 221 individuals had no confirmed identity following post-mortem and identification attempts. DNA samples (for identification and/or investigative purposes) were taken in a total of 490 cases, yet concerningly, these samples represented many people with a confirmed identity, and not all individuals without an (alleged) identity. Of the 221 unidentified human remains, only 62 (28 %) were afforded DNA analysis, suggesting an underutilisation of DNA analysis requests. This observation highlights a potential missed opportunity to leverage DNA technology more comprehensively in cases where conventional identification methods prove insufficient. Further, DNA results were only obtained for 64 cases (13.06 %) with results from 426 cases still outstanding seven years later. Where reports were available, identification via familial matching was successful in 95.31 % of cases (n = 61/64), leading to a success rate of 12.45 % (n = 61/490) for DNA as an identification tool. This poor success rate in 2015 could be attributed to several factors including: inadequate sampling post-mortem possibly due to unclear guidelines about which state authority was responsible for sampling, the low chances of a match on the National Forensic DNA Database due to its infancy (and thus containing few reference DNA profiles), next-of-kin not providing reference samples due to lack of awareness or fear of authorities, or inadequate infrastructure or access to resources. This study highlights the need for intentional and consistent sampling of unidentified human remains and calls for larger efforts to encourage next-of-kin to provide reference samples to increase the chances of identification.